LAW AND JUSTICE IN THE AGE OF POSTMODERNISM - Marius ANDREESCU; Andra PURAN (Challenges of the Knowledge Society)
This study represents an attempt to highlight, from a legal and philosophical perspective, the most significant contradictions that can affect justice during a period of social crisis, namely the era of postmodernism. The object of our analysis is: normativism and legal formalism, the ideology of globalisation, the contradiction between the consecration and guarantee of citizen rights and the restriction of their exercise through excess of power, the contradictions between law and justice; justice and society and the act of fulfilling justice and what we call the „outward fall of justice”. In this context, we refer to some aspects that characterise the person and personality of the judge. This essay is a plea for the principles of law as a possible solution to solve and overcome the crisis of law and justice in postmodernism. Starting from the difference between „given” and „constructed”, we propose the distinction between „metaphysical principles” external to law, which through their content have philosophical meanings, and „constructed principles” elaborated and normatively consecrated. We emphasise the obligation of the legislator, but also of the judge, to refer to the principles of law, including those external to law, in the legislative activity, interpretation and application of the law.